Ordering and interaction of molecules encapsulated in carbon nanotubes - Khlobystov, A; Porfyrakis, K; Britz, D; Kanai, M; Scipioni, R; Lyapin, S; Wiltshire, J; Ardavan, A; Nguyen-Manh, D; Nicholas, R; Pettifor, D; Dennis, T; et al. (2004)
A clear understanding of the interactions between the building blocks of self-assembled molecular materials is essential for rational design of functional nanostructures. Intermolecular interactions have been investigated for three different classes of fullerenes in single-walled carbon nanotubes (SWNTs); van der Waals molecule - molecule and molecule - SWNT interactions control the geometry of the molecular arrays inside nanotubes; electrostatic intermolecular forces influence the alignment of polar endohedral fullerenes M@C82; and hydrogen bonding between functionalised fullerenes has a significant effect on the selectivity of insertion of functionalised fullerenes into SWNTs.